Answer:
Part 1) [tex]C=90\°[/tex]
Part 2) [tex]A=63\°[/tex]
Part 3) [tex]b=6.8\ units[/tex]
Part 4) [tex]a=13.4\ units[/tex]
Step-by-step explanation:
step 1
Find the measure of angle C
we know that
The triangle ABC is a right triangle
so
Angle C is a right angle
therefore
[tex]C=90\°[/tex]
step 2
Fin the measure of angle A
we know that
In the right triangle ABC
∠B+∠A=90° -----> by complementary angles
we have
[tex]B=27\°[/tex]
substitute
[tex]27\°+A=90\°[/tex]
[tex]A=63\°[/tex]
step 3
Find the length side b
we know that
In the right triangle ABC
[tex]sin(B)=b/c[/tex]
[tex]b=(c)sin(B)[/tex]
substitute the given values
[tex]b=(15)sin(27\°)=6.8\ units[/tex]
step 4
Find the length side a
we know that
In the right triangle ABC
[tex]sin(A)=a/c[/tex]
[tex]a=(c)sin(A)[/tex]
substitute the given values
[tex]a=(15)sin(63\°)=13.4\ units[/tex]
Answer:
A = 63 , a = 13.4, b = 6.8
Step-by-step explanation:
I need help please it’s hard for me
Answer:
A, B, and D
Step-by-step explanation:
A
= 2x+3 < 10
= 2(3)+3 < 10
= 9<10
true
B
= 2x - 3 < 4
= 2(3) -3 < 4
= 3 < 4
true
C
= 5 + 3x > 15
= 5 + 3(3) > 15
= 14 > 15
not true
D
= 12-3x > 2
= 12 - 3(3) > 2
= 3 > 2
true
Select all the correct answers.
GroGain and FolliclePlus are hair regrowth systems. Each company claims that the application of their product will cause hair regrowth
for balding men. A barber decided to test each company's claim. He randomly selected 30 of his customers who had similar balding
issues and asked 15 of them to use GroGain and 15 of them to use FolliclePlus.
After observing the men for six months, the barber reported that, on average, those who used GroGain had a 20% increase in hair
regrowth and those who used FolliclePlus had a 10% increase in hair regrowth.
Which of the following statements are true?
FolliclePlus is the more effective hair regrowth system because it yielded a greater hair
regrowth increase percentage.
O
GroGain is the more effective hair regrowth system because it yielded a lower hair
"regrowth increase percentage.
GroGain is the more effective hair regrowth system because it yielded a greater hair
regrowth increase percentage.
FolliclePlus's claim is true.
FolliclePlus is the more effective hair regrowth system.
GroGain's claim is true.
Answer:
GroGain is the more effective hair regrowth system because it yielded a greater hair
Step-by-step explanation:
Answer
FolliclePlus's claim is true
GroGrain's claim is true
GroGrain is the more effective hair regrowth system because it yielded a greater hair growth increase precentage
Step-by-step explanation:
PLATO
A man walked north 119 feet and then west 120 feet. Find the shortest distance between the start and end points.
Answer:
169 feet
Step-by-step explanation:
(see attached)
What is the value of -3+8 when x=4
Solve this equation. Solve for the letter X
-×=-34
Answer: x=34
Step-by-step explanation: Divide each side by -1 to get rid of the negatives and isolate x. You will get x = 34 as your answer.
A famous instance of variation is Newton’s Law of Gravity. It states that the magnitude of the Force, F, of gravitational attraction between two masses, m1 and m2, varies directly with the product of the masses and inversely with the square of the distance, r, between them. Write a variation equation relating F, m1, m2, and r.
[tex]\bf \qquad \qquad \textit{combined proportional variation} \\\\ \begin{array}{llll} \textit{\underline{y} varies directly with \underline{x}}\\ \textit{and inversely with \underline{z}} \end{array}\implies y=\cfrac{kx}{z}\impliedby \begin{array}{llll} k=constant\ of\\ \qquad variation \end{array} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ F=\cfrac{k(m_1\cdot m_2)}{r^2}\leftarrow \textit{F varies directly with a product and inversely with }r^2[/tex]
Solve the compound inequality 6b < 36 or 2b + 12 > 6.
Answer:
all values of b
Step-by-step explanation:
6b < 36 or 2b + 12 > 6.
First solve the one on the left
6b < 36
Divide by 6
6b/6 < 36/6
b <6
Then solve the one on the right
2b + 12 > 6
Subtract 12 from each side
2b+12-12 >6-12
2b >-6
Divide by 2
2b/2 >-6/2
b >-3
b<6 or b >-3
Rewriting
b>-3 or b<6
b > -3 is an open circle at -3 with a line going to the right
b < 6 is an open circle at 6 with a line going to the left
The or means we add the lines together
We have a line going from negative infinity to infinity
all values of b
Answer:
All real numbers b ∈ [tex](-\infty, \infty)[/tex]
Step-by-step explanation:
First we solve the following inequality
[tex]6b < 36[/tex]
Divide by 6 both sides of the inequality
[tex]b<\frac{36}{6}\\\\b<6[/tex]
The set of solutions is:
[tex](-\infty, 6)[/tex]
Now we solve the following inequality
[tex]2b + 12 > 6[/tex]
Subtract 12 on both sides of the inequality
[tex]2b + 12-12 > 6-12[/tex]
[tex]2b> -6[/tex]
Divide by 2 on both sides of the inequality
[tex]\frac{2}{2}b> -\frac{6}{2}[/tex]
[tex]b> -3[/tex]
The set of solutions is:
[tex](-3, \infty)[/tex]
Finally, the set of solutions for composite inequality is:
[tex](-\infty, 6)[/tex] ∪ [tex](-3, \infty)[/tex]
This is: All real numbers [tex](-\infty, \infty)[/tex]
true or false ? The segment ab is congruent to the segment bo
Answer:
True
Step-by-step explanation:
The segment ¯AB¯ is congruent to the segment ¯BC¯ .
The point is in between the circle.
Therefore, they are congruent.
True. The segment AB is congruent to the segment BC.
How to know two line segments are congruent ?If the length of both the line segments are same, then we can say that both the line segments are congruent to each other.
Is the statement true or false ?Here, in the given diagram AC is a chord of the circle centering at O.
B is a point on the chord AC.
The radius of the circle which is perpendicular to AC & passes through B,forms right angle at point B.
Since, AC is a chord of the circle & a radius is perpendicular to AC, the the intersecting point of AC & the radius is midpoint of AC.
So, B is the midpoint of AC.
∴ Line segment AB = Line segment BC
Hence, Segment AB is congruent to segment BC.
Learn more about congruent line here :
https://brainly.com/question/22359139
#SPJ2
Michelle is on a secret mission to reclaim artifacts that were recently stolen from the National Museum. The artifacts are located in a private manor just outside the city. The rectangular base of the manor is 60m by 30m.
Help Michelle plan her mission by redrawing the base of the manor by moving points on the grid below.
HELP!!
The drawing should be 10 units in width and 5 units in height.
What is problem-solving?Problem-solving is the act of defining a problem; figuring out the purpose of the trouble; identifying, prioritizing, and selecting alternatives for an answer; and imposing an answer.
What are problem-solving and examples?Problem-solving starts with identifying the issue. As an example, a trainer may need to parent out a way to improve a scholar's overall performance on a writing talent test. To do that, the instructor will overview the writing exams looking for regions for improvement.
Learn more about Problem-solving here: brainly.com/question/13818690
#SPJ2
There are 6 students participating in a poetry contest, in how many ways can the students who go first and second in the bee be chosen?
Answer:
There are are 30 possible ways for the 6 students to be ranked 1st and 2nd
Step-by-step explanation:
There are 6 students, and any of them could receive first place. Therefore, there are 6 possibilities for first place.
A student cannot receive first and second place, so the student who won first place cannot also win second place. Therefore, there are only 5 students who could win second place.
We can multiply these two possibilities to find the number of possible rankings of 1st and 2nd
6*5=30
There are are 30 possible ways for the 6 students to be ranked 1st and 2nd....
If X plus 5 equals 8, then what is X?
Answer:
X plus 5 equals 8, then whats is X. The answer would be X = 3
Step-by-step explanation: Hope it helps
Answer:
x = 3Step-by-step explanation:
[tex]x+5=8\qquad\text{subtract 5 from both sides}\\\\x+5-5=8-5\\\\x=3\\\\Check:\\\\3+5=8\qquad CORRECT :)[/tex]
Alex and Alicia are twins. Kevin is 5 years older than the twins. Their ages total 53. How old are the twins?
what is the constant variation of k, of the direct variation, y=kx, through (5,8)
Answer:
The constant of variation is 1.6.
Step-by-step explanation:
y = kx and x = 5 when y = 8 and k = the constant of variation.
8 = k*5
k = 8.5 = 1.6.
Answer:
8/5
Step-by-step explanation:
Plug in the point given into
y=kx.
The number you get for y will be your constant of variation, also know as constant of proportionality.
(x,y)=(5,8) implies 8=k(5)
So in solving that equation we just need to divide both sides by 5 giving us:
8/5=k.
through: (2,2), parallel to y=x+42)
Answer:
y=x
Step-by-step explanation:
We want a line parallel to y =x+42
The slope of y =x+42 is 1
Parallel lines have the same slope
We have the slope m=1 and a point (2,2)
We can use point slope form to write a line
y-y1 = m(x-x1)
y-2 = 1(x-2) point slope form
Changing to slope intercept form
y-2 = x-2
Add 2 to each side
y-2+2 = x-2+2
y=x
The line parallel to y = x + 42 travels through (2,2) can be represented by the equation y = x. This conclusion is based on the principles of line equations in a two-dimensional space, with slopes determining the parallelism of lines.
Explanation:The subject of the question pertains to the formula of a line in a two-dimensional space. Specifically, you're asked to find a line that passes through the point (2,2) and is parallel to the line described by the equation y = x + 42.
In a standard equation of a line, y = mx + b, 'm' represents the slope of the line and 'b' indicates the y-intercept. Two lines are parallel if they have the same slope. Bearing this in mind, as the line y = x + 42 has a slope of 1 (since 1 is the coefficient of 'x'), the required line would also possess a slope of 1.
Substituting the point coordinates (2,2) into the equation y = mx + b (replacing 'm' with 1), gives us 2 = 2 + b. Solving for 'b', we find that it equals zero. Hence, the equation of a line parallel to y = x + 42 passing through the point (2,2) is y = x.
Learn more about Line Equation here:https://brainly.com/question/21511618
#SPJ3
PLEASE HELP
Confirm that f and g are inverses by showing that f(g(x)) = x and g(f(x)) = x.
f(x) = x3 + 4 and g(x) = Cube root of quantity x minus four.
any other details you could give me ?
It is proved that f and g are inverses by showing that f(g(x)) = x and g(f(x)) = x.
What are inverse function?
An inverse function is a function that returns the original value for which a function has given the output.
How to confirm that f and g are inverses ?According to the problem,
f(x) = x³ + 4 g(x) = [tex]\sqrt[3]{x-4}[/tex]Now, f(g(x)) = [tex](\sqrt[3]{x-4})^{3} + 4[/tex] = x
g(f(x)) = [tex]\sqrt[3]{x^{3}+4 -4}[/tex] = x
Thus it is proved that f and g are inverse functions.
Find more about "Inverse Functions" here: https://brainly.com/question/1144043
#SPJ2
prescription for marilyn jones piroxicam 20 mg capsule take 1 capsule 2 times a day how many milligrams mg will marilyn take of the Piroxicam in 90 days
Answer:
she will be taking 3600 mgs. in 90 days
Step-by-step explanation:
if she is taking a 20 mgs. twice a day that will make it 40 mgs. a day. If she takes it for 90 days
you will multiply 90 by 40
so
90
x40
= 3600 mgs. in 90 days
Answer:
3600 mg
Step-by-step explanation:
She takes 1 capsule 2 times a day
2* 20 mg = 40 mg
She takes 40 mg a day
She takes them for 90 days
40 mg a day for 90 days
40*90
3600 mg
Which is the graph of the equation y-1=2/3(x-3)?
PLEASE ANSWER ASAP
Answer:
Graph #1
Step-by-step explanation:
Compare your
y - 1 = (2/3)(x - 3) to
y - k = m(x - h). We see that k = 1 and h = 3.
Thus, (1, 3) is a point on the graph. This matches Graph #1.
Note: Graph #1 and Graph #3 appear to be the same. Why?
The graph of the equation is:
Graph 1
Step-by-step explanation:The equation is given by:
[tex]y-1=\dfrac{2}{3}\times (x-3)[/tex]
Now, we will see the point through which the graph passes through.
when x=3 we have:
[tex]y-1=\dfrac{2}{3}\times (3-3)\\\\i.e.\\\\y-1=\dfrac{2}{3}\times 0\\\\i.e.\\\\y-1=0\\\\i.e.\\\\y=1[/tex]
i.e. the graph passes through (3,1)
and also when x= -3 we have:
[tex]y-1=\dfrac{2}{3}\times (-3-3)\\\\i.e.\\\\y-1=\dfrac{2}{3}\times -6\\\\i.e.\\\\y-1=2\times -2\\\\i.e.\\\\y-1=-4\\\\i.e.\\\\y=-4+1\\\\i.e.\\\\y=-3[/tex]
i.e. the graph passes through (-3,-3)
The graph which satisfies these two points is: Graph 1
A writer chargers $5 per word plus a startup fee of $50 per article. Write an equation in standard form to represent the total cost, y of a project that is x words long
Answer:
The answer is y=5x+50
Hope this helps!!!
The equation -2x2-8x = 10is rewritten in the form of -2(x-p)2+q = 0. What is the value of q?
Answer:
q = -2
Step-by-step explanation:
-2x²-8x = 10 (divide both sides by -2)
x² + 4x = -5 (Apply completing the square method)
x² + 4x + (4/2)²= -5 + (4/2)²
x² + 4x + 2²= -5 + 2² (reduce left hand side using a²+2ab+b² = (a+b)² )
(x+2)² = -5 +4
(x+2)² = -1
(x+2)² + 1 = 0 (multiply both sides by -2)
(-2)(x+2)² + 1 (-2) = 0
-2[x - (-2)]² + (-2) = 0 ---> compare this with -2(x-p)² + q = 0
We can see that p = 2 and q = -2
The value of 'q' in the rearranged form of the given quadratic equation -2(x-p)²+q = 0 is -6. This is obtained by completing the square and comparing the equations.
Explanation:Given the quadratic equation -2x² -8x = 10, it's rearranged to the form -2(x-p)²+q = 0. The objective is to find the value of 'q'.
To achieve this, you first need to rewrite the given equation -2x² -8x - 10 = 0 in the form -2(x-h)²+k = 0. This is called completing the square. The 'h' value here is equal to -b/2a, where 'b' is the coefficient of 'x' and 'a' is the coefficient of x². In this equation, a is -2 and b is -8 so h=(-(-8)/(2×(-2))=8/4=2.
Substituting h into the equation, you have -2(x-2)²+k=0. Now expand and simplify to get -2x²+8x-4+k=0. Comparing this with the original equation -2x² -8x -10 = 0, you can see that 'k' is equal to -10+4=-6, which is the 'q' value in the form -2(x-p)²+q = 0. So, the value of 'q' is -6.
Learn more about Quadratic Equations here:https://brainly.com/question/30098550
#SPJ2
Is the following graph linear, nonlinear and/or a relation?
Answer:
B. Linear function and a relation
Step-by-step explanation:
The graph is a straight line and by definition a linear function.
Each point on the line can be expressed as an ordered pair i.e the coordinates (x,y), implying that there is a relation between x and y.
Answer:
B. Linear function and a relation
Step-by-step explanation:
The following terms are defined like so,
Linear: linear functions show up as straigh lines when plotted on a graph
Non-Linear: non-linear functions show up as curvy or wavvy lines when plotted on a graph
Relation: relation graphs have specific outputs for every input, meaning for every x location on the graph there is only one y point.
Based on the definitions above we can determine that the graph in the diagram is both Linear and a Relation, since it is both a straight diagonal line as well as only having one specific y coordinate for every x coordinate. So the answer would be B. Linear function and a relation.
I hope this answered your question. If you have any more questions feel free to ask away at Brainly.
What is the solution of the equation x2 + 8x + 5 = 0?
Answer:
x = -0.683 (3dp)
x = -7.317 (3dp)
Step-by-step explanation:
Step 1: Apply the quadratic formula
(-b±([tex]\sqrt{b^{2}-4ac}[/tex])) / 2a
a = 1 (x²)
b = 8 (8x)
c = 5 (5)
(-8±([tex]\sqrt{8^{2}-4 x 1 x 5}[/tex])) / 2 x 1
Step 2: Simplify
(-8±([tex]\sqrt{44}[/tex])) / 2
Step 3: Solve
You need to replace the ± with first a + and then a -.
(-8+([tex]\sqrt{44}[/tex])) / 2 = -0.683 (3dp) = x
(-8-([tex]\sqrt{44}[/tex])) / 2 = -7.317 (3dp) = x
Hope this helps!
What is the average rate of change for the sequence shown below? coordinate plane showing the points 1, 4; 2, 2.5; 3, 1; and 4, negative 0.5
Answer:
-1.5
Step-by-step explanation:
So your set of points I believe is:
(1,4)
(2,2.5)
(3,1)
(4,-0.5)
You are asked to find the average rate of change. This just means find the slope.
So you can make sure the slope is the same per pair of points.
So I like to find the slope by lining two points up vertically and subtracting vertically then put 2nd difference over 1st difference.
(2 , 2.5)
-( 1 , 4)
----------------
1, -1.5
So the slope is -1.5/1 or just -1.5.
Check another pair:
(3 , 1 )
- (2 ,2.5)
------------
1 , -1.5
So the slope is -1.5/1 or just -1.5.
Check one more:
(4 , -.5)
-(3 , 1)
-----------
1, -1.5
So the slope is -1.5 or just -1.5
So the average rate of change is -1.5.
Graph -3x + 9y = -27
Answer:
So the x-intercept is (9,0) and the y-intercept is (0,-3).
So I'm going to graph both points and connect them with a straight-edge.
Step-by-step explanation:
I would graph this using it's x- and y-intercepts.
To find the x-intercept, set y=0.
-3x+9(0)=-27
-3x+0=-27
-3x=-27
Divide both sides by -3:
x=9
To find the y-intercept, set x=0:
-3(0)+9y=-27
0 +9y=-27
9y=-27
Divide both sides by 9:
y=-3
So the x-intercept is (9,0) and the y-intercept is (0,-3).
So I'm going to graph both points and connect them with a straight-edge.
how many sides does a regular nanogon have? A.7 B. 8 C.6 D.9
Well, by definition, it's 9-sided polygon, so the answer should be obvious ;)
Answer:
D
Step-by-step explanation:
A regular nonagon is a nine-sided shape with equal sides and equal angles of 140 degrees each. Each interior angle measure of a regular nonagon is 140 degrees.
What is the verbal expression for 3(n+8)
Make n be a number. You must add 8 and the number together then multiply the answer by 3. This means that the verbal expression is:
3 multiplied by the sum of a number and 8.
Hope this helped!
~Just a girl in love with Shawn Mendes
Like terms can be added or subtracted true or false
Solve for x. Your answer must be simplified. -12x ≤ 44
Answer:
x ≥ - [tex]\frac{11}{3}[/tex]
Step-by-step explanation:
Given
- 12x ≤ 44
Divide both sides by - 12, remembering to reverse the inequality sign as a consequence of dividing by a negative quantity, hence
x ≥ [tex]\frac{44}{-12}[/tex] ← note sign reversed
Dividing the numerator/denominator by 4, gives
x ≥ - [tex]\frac{11}{3}[/tex]
(Pictures included, pls help)
Carlos draws a transversal, t, on two parallel lines AB and CD, as shown below:
He makes the following table to prove that the alternate interior angles are equal:
Which is The missing justification?
A) Opposite Interior Angles Are congruent when parallel lines are intersecting by a transversal
B) Vertical Angles Formed By Two Intersecting Segments Are Congruent
C) Adjacent Angles Formed By Two Interesting Segments Are Supplementary
D) Opposite Exterior Angles Are Congruent When Parallel Lines Are Intersected By A transversal
Answer:
Option B
Step-by-step explanation:
When two intersecting lines cut each other they form four angles. these two pair of angles are called opposite angles or vertical angles. The vertical angles formed by two intersecting segments are equal.
Thus option B is correct: The vertical Angles Formed By Two Intersecting Segments Are Congruent !
Answer:
B.
Step-by-step explanation:
When you intersect two lines, the angles opposite by the intersection vertex has the same measure. Generally, Those angles are called vertical angles.
In the figure, we have that angle 1 and angle 3 are vertical angles, then both have the same measure. So, the correct option is B) Vertical Angles Formed By Two Intersecting Segments Are Congruent.
What is the prime factorization of 621?
Answer:
The prime factors of 621 are 3*3*3*23 ....
Step-by-step explanation:
Prime factorization is the process of finding that which prime numbers can be multiplied together to make the original number.
Find the prime factors of 621.
Start with the smallest prime number which is 2. If the number is divisible by 2 then solve further. If not then move to the next prime number.
621 is nor divisible by 2
We move towards the next prime number which is 3.
621 divided by 3 = 207
207 divided by 3 = 69
69 divided by 3 = 23
Now 23 is only divisible by 23 which is also a prime number.
Thus the prime factors of 621 are 3*3*3*23 ....
What is the solution to the equation 1/4x+2=-5/8x-5
Answer:
-8
Step-by-step explanation:
Start by multiplying both sides by 4.
[tex]\frac{1}{4} x+2=-\frac{5}{8} x-5\\x+8=-\frac{5}{2} x-20[/tex]
Next, multiply both sides by 2.
[tex]x+8=-\frac{5}{2} x-20\\2x+16=-5x-40[/tex]
Now, combine like terms.
[tex]2x+16=-5x-40\\7x+16=-40\\7x=-56\\x=-8[/tex]
Answer:
-8 on edg
Step-by-step explanation: